1996
DOI: 10.1038/bjc.1996.51
|View full text |Cite
|
Sign up to set email alerts
|

Vascular perfusion and hypoxic areas in RIF-1 tumours after photodynamic therapy

Abstract: Summary The influence of photodynamic therapy (PDT) on vascular perfusion and the development of hypoxia was investigated in the murine RIF-I tumour. Image analysis was used to quantify changes in perfusion and hypoxia at 5 min after interstitial Photofrin-mediated PDT. The fluorescent stain Hoechst 33342 was used as an in vivo marker of functional vascular perfusion and the antibody anti-collagen type IV as a marker of the tumour vasculature. The percentage of total tumour vasculature that was perfused decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…Consistent with the above observations, no differences were found in tumour perfusion after high-or low-fluence-rate PDT. In both cases, tumour perfusion progressively decreased with time after treatment as has been described by others (Roberts et al, 1994;van Geel et al, 1994van Geel et al, , 1996. However, marked differences were found in cutaneous perfusion.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the above observations, no differences were found in tumour perfusion after high-or low-fluence-rate PDT. In both cases, tumour perfusion progressively decreased with time after treatment as has been described by others (Roberts et al, 1994;van Geel et al, 1994van Geel et al, , 1996. However, marked differences were found in cutaneous perfusion.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous reports have shown that PDT induces microvascular damage within treated tumors (3 -5) and that this leads to tumor hypoxia (4,11). Because hypoxia induces increased expression and stabilization of HIF-1a and activates the HIF-1 transcription factor, recent molecular studies have thus far investigated the effects of PDTinduced hypoxia on expression of proangiogenic factors and their relevance to treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen levels gradually decreased due to PDT-induced photochemical oxygen consumption. However, the oxygen concentration in the medium surrounding the cells remained high throughout 4 http://rsb.info.nih.gov/ij/ the treatment fluence of 2.5 J cm À2 and never decreased below 90% of the air-saturated level. These experiments thus confirmed that transient hypoxia was not induced under these PDT irradiation conditions.…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations